2019
DOI: 10.2147/cmar.s226050
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combined Use of Mean Platelet Volume/Platelet Count Ratio and Platelet Distribution Width to Distinguish Between Patients with Nasopharyngeal Carcinoma, Those with Benign Tumors of the Nasopharynx, and Healthy Subjects</p>

Abstract: PurposeFor the diagnosis of nasopharyngeal carcinoma (NPC), reliable early indicators with sensitivity and specificity should be sought. This study evaluated the effect of the combined use of mean platelet volume/platelet count ratio (MPV/PC ratio) and platelet distribution width (PDW) for differential diagnosis of NPC. In this study, MPV/PC ratio was used for the first time to diagnostically evaluate NPC.Patients and methodsWe retrospectively analyzed various hematological indices of three subject groups (208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In our study, we found low MPV/PC ratios were associated with disease progression. Furthermore, the value of the MPV/PC ratio dropped stepwise from early to late stages, which is supported by Zhang et al [21]. Moreover, the C-index, which added the pathological stage as a known prognostic factor, showed that the AUC of the MPV/PC ratio in our study was 0.912 (p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, we found low MPV/PC ratios were associated with disease progression. Furthermore, the value of the MPV/PC ratio dropped stepwise from early to late stages, which is supported by Zhang et al [21]. Moreover, the C-index, which added the pathological stage as a known prognostic factor, showed that the AUC of the MPV/PC ratio in our study was 0.912 (p < 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, substantial consumption of platelets happens in the case of inflammation or cancer. Overall, fluctuation of the PC may compromise its reliability for predicting disease progression [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a significant progress has been made in the study of hematological markers for prognosis of different tumors. [ 7 , 8 ] The hematological indices have been widely used as indicators for prognosis, which are highly reproducible and cost-effective for clinical use. [ 9 , 10 ] This study aimed to investigate the clinical significance of hemoglobin-to-red cell distribution width ratio (Hb/RDW), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) in the diagnosis of NPC.…”
Section: Introductionmentioning
confidence: 99%